Cloning, Nucleotide Sequence, and Expression of the Brucella melitensis sucB Gene Coding for an Immunogenic Dihydrolipoamide Succinyltransferase Homologous Protein - Zygmunt, Michel S. (American Society for Microbiology, 2001)
The Brucella melitensis sucB gene encoding the dihydrolipoamide succinyltransferase (E2o) enzyme (previously identified as an immunogenic protein in infected sheep) was cloned and sequenced. The amino acid sequence predicted from the cloned gene revealed 88.8 and 51.2% identity to the dihydrolipoamide succinyltransferase SucB protein from Brucella abortus and Escherichia coli, respectively. Sera from naturally infected sheep showed antibody reactivity against the recombinant SucB protein.